"FAST-TRACK" IN SIMULTANEOUS OPERATIONS AGAINST THE BACKGROUND OF WIDESPREAD PERITONITIS - V. Yu. Mykhaylichenko; O. Yu. Gerbali; U. I. Basnaev; N. E. Karakursakov (Кубанский научный медицинский вестник)
Aim. This research was conducted to study the possibility and effectiveness of the "Fast-track" fast recovery program application when performing simultaneous operations against the background of widespread peritonitis.Materials and methods. In the course of the study were examined 66 patients, the ratio of woman/man was 45:21. The main group – 32 (48,5%) patients with the major disease of constricted postoperative hernia complicated by the widespread peritonitis and chronic calculous cholecystitis (a prospective analysis of surgical treatment). The comparison group – 34 (51,5%) patients with the identical pathology – the retrospective analysis of surgical treatment. The treatment of patients of the main group was supplemented with the application of the elements of the «Fast-track» program. Whereas, the treatment of patients of the comparison group was performed exclusively according to the standard scheme of the patient management with widespread peritonitis.Results. Clinical, laboratory and instrumental data indicate the positive effect of the "Fast-track" program on the process of rehabilitation of patients in the postoperative period. There was a significant acceleration in the recovery of motorevacuation function of the intestine in patients of the main group in relation to the comparison group and a smaller number of complications in the main group in relation to the comparison group against the background of the application of this technique. As a result, the average duration of hospitalization of patients from the comparison group was 10- 5 days (average 12±2,4 days). While the average duration of hospitalization of patients from the comparison group was 17-20 days (on average 18±1,2 days).Conclusion. The use of the "Fast-track" program in simultaneous operations does not increase the effectiveness of surgical treatment, thereby accelerating the process of rehabilitation of patients in the postoperative period.